Diagnosis and Initial Investigation of Bronchiectasis - Amati, Francesco; Simonetta, Edoardo; Pilocane, Tommaso; Gramegna, Andrea; Goeminne, Pieter; Oriano, Martina; Pascual-Guardia, Sergi; Mantero, Marco; Voza, Antonio; Santambrogio, Martina; Blasi, Francesco; Aliberti, Stefano (Seminars in Respiratory and Critical Care Medicine, 2021)
Bronchiectasis refers to both the name of a disease and a single radiological appearance that may, or may not, be associated with disease. As chronic respiratory disease, bronchiectasis is characterized by a variable range of signs and symptoms that may overlap with other chronic respiratory conditions. The proper identification of bronchiectasis as a disease in both primary and secondary care is of paramount importance. However, a standardized definition of radiologically and clinically significant bronchiectasis is still missing. Disease heterogeneity is a hallmark of bronchiectasis and applies not only to radiological features and clinical manifestations but also to other aspects of the disease, including the etiological and microbiological diagnosis as well as the evaluation of pulmonary function. Although the guidelines suggest a “minimum bundle” of tests, the diagnostic approach to bronchiectasis is challenging and may be driven by the “treatable traits” approach based on endotypes and biological characteristics. A broad spectrum of diagnostic tests could be used to investigate the etiology of bronchiectasis as well as other pulmonary, extrapulmonary, and environmental traits. Individualizing bronchiectasis workup according to the site of care (e.g., primary, secondary, and tertiary care) could help optimize patients' management and reduce healthcare costs.
Keywords: bronchiectasis; etiology; treatable traits; phenotype; endotype